Venomous mollusks: the risks of human accidents by conus snails (gastropoda: conidae) in Brazil - Haddad Junior,Vidal (2006)
Mollusks of the genus Conus present a venomous apparatus composed of radulae, a chitin structure linked to glands, which injects potent neurotoxic peptides, causing serious human envenomation and even death, associated with the blockage of certain receptors and muscular paralysis. No reported envenomation has occurred in Brazil, but certain populations are at risk of accidents.